A Review on the Etiology, Prevention, and Management of Ureteral Injuries During Obstetric and Gynecologic Surgeries - Ade-Ojo IP; Tijani O (Dove Medical Press, 2021)
Idowu Pius Ade-Ojo,1 Olatoyosi Tijani2 1Department of Obstetrics Gynecology, Ekiti State University, Ado-Ekiti, Nigeria; 2Department of Obstetrics and Gynecology, Ekiti State University Hospital, Ado-Ekiti, NigeriaCorrespondence: Idowu Pius Ade-OjoDepartment of Obstetrics Gynecology, Ekiti State University, Ado-Ekiti, NigeriaTel +2348033886173Email ipadeojo@eksu.edu.ngAbstract: Iatrogenic ureteral injuries are a rare but serious complication of some gynecological and obstetric procedures with both high morbidity and legal implications. The incidence varies widely depending on the type and extent of the surgeries with about 70% unrecognized intraoperatively. When recognized intraoperatively and promptly managed, the prognosis is good. Ureteral injuries recognized postoperatively come with dire consequences for the patients and are litigation prone. Due to the proximity of the lower half of the ureters to the pelvic organs, 50% of the cases of injuries to the ureter occur within the jurisdiction of gynecological and obstetric practice. A good knowledge of the etiology, predisposing factors, appropriate surgical skills, proper identification of the course and deviation of the ureters, and intraoperative recognition of inadvertent damage to the ureter and its vasculature is required by all obstetricians and gynecologists to reduce the incidence of ureteral injuries by at least 50%. This review aims to add to what is already known, particularly among obstetricians and gynecologists practicing in resource-constrained settings.Keywords: ureteral injuries, obstetrics and gynecology